Efficacy, Safety, and Impact on the Quality of Life of Guselkumab in the Treatment of Moderate-to-Severe Plaque Psoriasis and Psoriatic Arthritis - Smereka, Szymon; Jabłoński, Wiktor; Raszewska, Julia; Wolińska, Natalia; Riccardi, Caterina (Dermatology Review/Przegląd Dermatologiczny, 2025)
Guselkumab, a monoclonal antibody that targets the interleukin-23 p19 subunit, has demonstrated considerable efficacy in the management of moderate-to-severe plaque psoriasis and psoriatic arthritis through the inhibition of inflammatory pathways that are central to disease pathology. Series of extensive analyses of clinical trials and real-world studies indicate significant improvements in Psoriasis Area and Severity Index scores due to guselkumab. In the category of maintaining long-term skin clearance, it also outperforms other antibodies such as adalimumab. The results of key clinical trials, including VOYAGE 1, VOYAGE 2, and NAVIGATE, demonstrate that guselkumab results in durable PASI 90 and PASI 100 responses and is associated with sustained improvements in the quality of life, as evidenced by reductions in scores on the Dermatology Life Quality Index and the Psoriasis Symptoms and Signs Diary. For patients with active psoriatic arthritis, the DISCOVER-1 and DISCOVER-2 studies demonstrate significant benefits in terms of joint symptom relief, thereby further consolidating guselkumab’s role as a comprehensive therapeutic agent. With a favorable safety profile, including low incidences of severe infections and minimal immunogenicity, guselkumab emerges as a reliable option for patients inadequately managed by other treatments. The objective of this work is to synthesize existing clinical findings in order to provide a comprehensive overview of guselkumab’s efficacy, safety, and impact on the quality of life in psoriasis and psoriatic arthritis, drawing solely on verified data from primary studies.